RIVAROXABAN IN THE PREVENTION OF THROMBOEMBOLIC COMPLICATIONS IN PATIENTS WITH ATRIAL FIBRILLATION - M. Yu. Gilyarov (Столичная издательская компания, 2015)
The possibilities of antithrombotic therapy in atrial fibrillation are highlighted. The alternative antithrombotic agents, including rivaroxaban presented along with the traditional drugs (acetyl-salicylic acid, warfarin). Efficacy and safety of rivaroxaban is considered on the basis of the results of the ROCKET-AF study.